Research progress on the effect of muscle satellite cells on anal sphincter repair in neurogenic fecal incontinence - He Jinchao; Wang Qunbo; Qin Qin; Zhao Ling; Dong Qingjun (结直肠肛门外科)
Neurogenic fecal incontinence refers to the dysfunction of anal sphincter contraction caused by degenerative atrophy of the anal sphincter secondary to pudendal nerve injury, manifested as involuntary leakage of feces from the anus. Muscle satellite cells are a group of adult stem cells in skeletal muscle that can be activated and differentiate into stem cells and myoblasts after skeletal muscle injury, reconstructing muscle fibers. The process of atrophy of the external anal sphincter is intimately linked to the number and activation-differentiation level of muscle satellite cells, and the activation and proliferation of muscle satellite cells play a pivotal role in the injury and regeneration of the anal sphincter. This process is regulated by the ecological niche and signal transduction of various cells and cytokines, serving as an important target for the treatment of neurogenic fecal incontinence. This article reviews the research progress on the effect of muscle satellite cells on anal sphincter repair in neurogenic fecal incontinence.